Magda Portal, el rol de la mujer y la poesía vanguardista de compromiso político en el Perú del siglo XX - Fernández Cozman, Camilo Rubén (2019)
Magda Portal (1900-1989) is one of the most representative Peruvian writers of the 20th century. He was a member of the Peruvian Aprista Party and defended the rights of women in a forgotten text: The Aprismo and the Woman (1933), where he uses the argument by exemplification to highlight the work of important women such as Clorinda Matto de Turner, Flora Tristán and María Alvarado Rivera He also practiced avant-garde poetry in A Hope and the Sea (1927) where he uses procedures such as metaphor, suppression of punctuation marks, blank page space and the use of various types of letters in order to question the androcentric order and contrast the masculine monolithic discourse against the diversity and richness of feminine discourse.